EMPOWERING EDUCATIONAL EXCELLENCE: THE CRITICAL ROLE OF SCHOOL LEADERS’ DEVELOPMENT PROGRAMS - Dr Rashmi Sumanth, (IJRDO- Journal of Educational Research, 2025)
The quality of education in schools is intricately linked to the effectiveness of school leadership. Despite widespread reforms in curricula, pedagogy, and technology integration, educational outcomes often fall short when school leaders lack the skills, vision, and support necessary to drive institutional excellence. This research addresses the pressing need to examine and enhance school leaders' development programs as a catalyst for educational transformation.School leadership plays a pivotal role in shaping school climate, influencing teacher performance, and ultimately driving student achievement. However, in many regions, leadership development remains fragmented, underfunded, or disconnected from real-world school challenges. The aim of this paper is to analyze the critical role of school leader development programs in achieving educational excellence. It evaluates existing frameworks, identifies gaps, and proposes actionable strategies for creating more impactful, context-specific training initiatives.Using a mixed-methods approach, the study incorporates survey data from school administrators, interviews with educators and policymakers, and a review of global best practices. The findings reveal that well-structured development programs enhance leadership capacity, promote data-driven decision-making, and foster a culture of continuous improvement. Furthermore, the study highlights the importance of mentorship, localized training content, and sustained policy support in building effective school leadership pipelines.This paper calls for a systemic shift in how educational systems perceive and invest in school leadership. By empowering leaders with the right tools and knowledge, we can transform schools into thriving ecosystems of learning and innovation.